Bank Loan Commitments and Corporate Leverage - Shockley, Richard L. (Journal of Financial Intermediation, 1995)
This paper investigates the relationship between a firm′s loan commitment demand and its overall capital structure. I develop a model which demonstrates that a loan commitment leads a firm to higher privately optimal debt level and a lower cost of debt funds; these results are driven by the loan commitment′s ability to attenuate the potential moral hazard problems attendant upon debt financing. I confront the predictions with cross-sectional data, and find that the availability of unused loan commitment financing is positively related to firm leverage and negatively related to cost of debt funds. Journal of Economic Literature Classification Numbers: D82, G21, G32.